Susceptibility to pulmonary disease due to Mycobacterium avium-intracellulare complex may reflect low IL-17 and high IL-10 responses rather than Th1 deficiency - Lim, A.; Allison, C.; Price, Patricia; Waterer, G. (Academic Press, 2010)
It remains unclear why some individuals and not others are susceptible to non-tuberculous mycobacterial lung disease (NTMLD). To determine whether NTMLD is associated with defects or biases in Th1/Th2/Th17 immunity, blood leukocytes from NTM patients with nodular bronchiectasis, their adult offspring, and healthy population controls were stimulated with staphylococcal enterotoxin B (SEB), tuberculin and sensitin to measure cytokine production. In response to SEB, NTM patients exhibited higher frequencies of IFN?-producing CD4 + T cells than population controls (P<0.001). In supernatant, levels of IL-17 were lower in patients than adult offspring. Sensitin elicited higher IFN? responses from patients than controls (P<0.05). Patients also produced more IL-10 in supernatant than controls after culture with tuberculin (P<0.01) or sensitin (P<0.05), but IL-10-producing CD4 + T cells were undetectable. NTMLD is not associated with deficient IFN? production, but may be associated with reduced Th17 immunity and/or a predisposition towards IL-10 production from non-CD4 + T cells. © 2010 Elsevier Inc.